Phenotypic variations in three sub-populations of Channa punctata (Bloch) of the Ganga basin - Singh, Minakshi; Sejauddin, M (Journal of the Inland Fisheries Society of India, 2021)
The specimens of Channa punctata (Bloch, 1793) were collected from three rivers (Gomti, Ganga, and Ken) of the Ganga basin characterized by different environmental gradients. The 21 phenotypic traits were studied and multivariate analysis was carried out to segregate the different stocks of C. punctata. A linear relationship was noted between different body measurements and total length in the fish of the three rivers studied. In ANOVA, 9 morphometric characters, out of 16, and 2 meristic traits, out of 5, were found to be significantly different among the populations of the three rivers indicating the presence of different stocks. The slopes of regression lines of morphometric measurements between the compared populations were also found to be significantly different at 0.1%, 1% and 5% levels of significance. Three populations were significantly different in body depth, head length, inter-orbital length, preanal length, dorsal fin length, pectoral fin length, caudal fin length, pre pelvic length, pelvic fin length, numbers of pectoral fin rays and caudal fin rays. The phenotypic differences in C. punctata may be due to genetically, ecologically, or lack of genetic mixing due to inhibition of fish movement.Key words Phenotypic character; meristic; intra-specific variation; Ken River